2008
DOI: 10.1111/j.1365-313x.2008.03552.x
|View full text |Cite
|
Sign up to set email alerts
|

SOC1 translocated to the nucleus by interaction with AGL24 directly regulates LEAFY

Abstract: SummarySUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (SOC1) is one of the flowering pathway integrators and regulates the expression of LEAFY (LFY), which links floral induction and floral development. However, the mechanism by which SOC1, a MADS box protein, regulates LFY has proved elusive. Here, we show that SOC1 directly binds to the distal and proximal region of the LFY promoter where critical cis-elements are located. Intragenic suppressor mutant analysis shows that a missense mutation in the MADS box of SOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
268
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(290 citation statements)
references
References 55 publications
(81 reference statements)
10
268
1
7
Order By: Relevance
“…We also analyzed the mRNA levels of Fv LFY and Fv AGL24, since SOC1 has been reported to bind directly to the promoters of LFY and AGL24 to activate their expression and to advance flowering in Arabidopsis (Lee et al, 2008;Liu et al, 2008). Constitutive overexpression of Fv SOC1 did not affect Fv LFY mRNA expression in the SD strawberry background, whereas Fv AGL24 tended to be slightly upregulated in Fv SOC1-OX lines compared with nontransgenic SD strawberry ( Figures 4D and 4E).…”
Section: Fv Soc1 Overexpression Represses Flowering In Strawberrymentioning
confidence: 99%
See 1 more Smart Citation
“…We also analyzed the mRNA levels of Fv LFY and Fv AGL24, since SOC1 has been reported to bind directly to the promoters of LFY and AGL24 to activate their expression and to advance flowering in Arabidopsis (Lee et al, 2008;Liu et al, 2008). Constitutive overexpression of Fv SOC1 did not affect Fv LFY mRNA expression in the SD strawberry background, whereas Fv AGL24 tended to be slightly upregulated in Fv SOC1-OX lines compared with nontransgenic SD strawberry ( Figures 4D and 4E).…”
Section: Fv Soc1 Overexpression Represses Flowering In Strawberrymentioning
confidence: 99%
“…In addition to the photoperiodic pathway, SOC1, as well as FT, integrates signals from the vernalization, autonomous, and GA flowering pathways (Lee et al, 2000;Moon et al, 2003Moon et al, , 2005Li et al, 2008;Jung et al, 2012). SOC1 interacts with multiple MADS box proteins, including AGAMOUS LIKE24 (AGL24), FRUITFUL (FUL), and AP1, and regulates the expression of several flowering genes, such as SHORT VEGETATIVE PHASE, AGL15, and AGL18, by directly binding to their regulatory sequences (de Folter et al, 2005;Lee et al, 2008;Seo et al, 2009;Immink et al, 2012;Tao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it is pertinent to make a conclusion that LFY may partly mediate the PKL regulation of flowering time control via chromatin modification. Interestingly, AGL24 and SOC1 regulate each other and act together to activate LFY transcription (Liu et al, 2008;Lee et al, 2008) while both AGL8/FUL and LFY are independent downstream targets of SPL3 in flowering time and meristem identity control (Yamaguchi et al, 2009). Both SOC1 and LFY are direct targets of AGL8/FUL that binds to a region 2.2 kb upstream to the ATG codon of the LFY gene (Balanza et al, 2014), overlapping with a previously identified region that is also bound by SOC1 (Lee et al, 2008).…”
Section: How Does Pkl Regulate Lfy Expression?mentioning
confidence: 99%
“…Interestingly, AGL24 and SOC1 regulate each other and act together to activate LFY transcription (Liu et al, 2008;Lee et al, 2008) while both AGL8/FUL and LFY are independent downstream targets of SPL3 in flowering time and meristem identity control (Yamaguchi et al, 2009). Both SOC1 and LFY are direct targets of AGL8/FUL that binds to a region 2.2 kb upstream to the ATG codon of the LFY gene (Balanza et al, 2014), overlapping with a previously identified region that is also bound by SOC1 (Lee et al, 2008). In this context of relationship with LFY, AGL8 and AGL24 may likely be involved in PKL-regulated flowering time control in spite of being the direct targets of PKL in addition to the involvement of LFY.…”
Section: How Does Pkl Regulate Lfy Expression?mentioning
confidence: 99%
“…At this stage of development (i.e., using a sampling time at 6 h after onset of the light period), the mRNA levels of CONSTANS (CO), SUPPRESSOR OF CO1 (SOC1), and AGL24 (e.g., Lee et al, 2008) were similar in swp73a and the wild type, whereas transcript amount of TFL1 (TERMINAL FLOWER1; a negative regulator of FD/FT-induced gene expression; Hanano and Goto, 2011) was about 2-fold lower in swp73a plants compared with the wild type. By contrast, in the swp73b mutant, a moderate (;1.8-fold) increase in FLC expression was observed, which was substantially less compared with the 5-fold increase reported by Jégu et al (2014) in the BAF60/SWP73B RNAi lines under SD.…”
Section: Swp73a and Swp73b Play Distinct Roles In Flowering Time Controlmentioning
confidence: 99%